The world's strongest librarian [large type] : a memoir of Tourette's, faith, strength, and the power of family - Hanagarne, Josh, 1977- (Thorndike Press, 2013)
Diagnosed with Tourette Syndrome when he was a high school freshman, Josh Hanagarne tried every remedy until an autistic strongman taught him to "throttle" his symptoms. Illuminating the mysteries of this little-understood disorder as well as his very different roles as strongman and librarian with humor and candor, this unlikely hero traces his journey to overcome his disability - and navigate his wavering Mormon faith - to find love and create a life worth living.